American Federation of Arts : 2001 exhibitions program. - Brown, Julia; Padon, Thomas; Ramljak, Suzanne (New York : American Federation of Arts, 2001)
Duchamp, Marcel ; Demuth, Charles ; Avery, Milton ; Whiteread, Rachel ; Kiefer, Anselm ; Warhol, Andy ; Nauman, Bruce ; Currin, John ; Byars, James Lee ; Oursler, Tony ; Gursky, Andreas ; Koons, Jeff ; Lawler, Louise ; Gonzalez-Torres, Felix ; Heald, David ; Ruff, Thomas ; James, Geoffrey ; Jenshel, Len ; Fischli & Weiss ; Gillick, Liam ; Lucas, Sarah ; Shrigley, David ; Taylor-Wood, Sam ; Billingham, Richard ; Saarinen, Eliel ; Saarinen, Eero ; Laib, Wolfgang
rondreizende tentoonstellingen p. 86-88, lijst exhibition department p. 89-91, lijst gastcuratoren p. 92-95, institutionele leden p. 100-106
Engels
boek